2017
DOI: 10.1002/2017jd026581
|View full text |Cite
|
Sign up to set email alerts
|

Improving representation of canopy temperatures for modeling subcanopy incoming longwave radiation to the snow surface

Abstract: A comprehensive analysis of canopy surface temperatures was conducted around a small and large gap at a forested alpine site in the Swiss Alps during the 2015 and 2016 snowmelt seasons (March–April). Canopy surface temperatures within the small gap were within 2–3°C of measured reference air temperature. Vertical and horizontal variations in canopy surface temperatures were greatest around the large gap, varying up to 18°C above measured reference air temperature during clear‐sky days. Nighttime canopy surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 32 publications
(77 reference statements)
3
33
0
Order By: Relevance
“…This result is because α IIS bs characterizes the surface intrinsic reflection property that is related to incident solar zenith, as α HHF bs depends on the SZA over the horizontal surface. Although some different patterns occur at the α IIS bs of sparse discontinuous forest over a large slope due to the canopy gap effect (Webster et al, 2017), similar surface albedo patterns are observed for medium and dense forests ( Figures S1-S3). The maximum absolute (relative) differences between α HHS bs and α IIS bs are up to 0.026 (61.8%), 0.134 (62.4%), and 0.114 (62.3%) in the VIS, NIR, and SW broadbands over a 60°sloped surface.…”
Section: /2018jd028283supporting
confidence: 60%
“…This result is because α IIS bs characterizes the surface intrinsic reflection property that is related to incident solar zenith, as α HHF bs depends on the SZA over the horizontal surface. Although some different patterns occur at the α IIS bs of sparse discontinuous forest over a large slope due to the canopy gap effect (Webster et al, 2017), similar surface albedo patterns are observed for medium and dense forests ( Figures S1-S3). The maximum absolute (relative) differences between α HHS bs and α IIS bs are up to 0.026 (61.8%), 0.134 (62.4%), and 0.114 (62.3%) in the VIS, NIR, and SW broadbands over a 60°sloped surface.…”
Section: /2018jd028283supporting
confidence: 60%
“…Additional testing should also better characterize the insulation properties of ground cover under different management scenarios. Third, the calculation of T rad is simple and applicable in data-sparse environments, but other approaches for adjusting a temperature value based on topography and land cover are available (Fox, 1992;Kang, 2005;Webster et al, 2017) and could be further tested. Fourth, future research should also determine the effects of spatial heterogeneity of snow and frost depth on runoff and streamflow at both the local and watershed scales.…”
Section: Resultsmentioning
confidence: 99%
“…The forest canopy also affects the amount of long‐wave radiation reaching an animal from above (Webster, Rutter, & Jonas, ). In the absence of a canopy, long‐wave radiation from the air ( L a ) is calculated as (Buckley, ; Campbell & Norman, ; Sears et al, ):Lnormala=εacσTnormalanormalinormalr+2734…”
Section: Methodsmentioning
confidence: 99%
“…where ε ac is clear‐sky emissivity. Under a canopy, long‐wave radiation ( L a,sub ) comes from the sky and from the canopy, in proportion to the amount of clear sky (Webster et al, ):La,sub=VnormalsLnormala+1-VsεnormalcσTnormalcnormalanormaln+2734…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation